Magnetic properties of microwave-plasma (thermal) chemical vapour deposited Co-filled (Fe-filled) multiwall carbon nanotubes: comparative study for magnetic device applications. (4th July 2018) - Mathur, A; Maity, Tuhin; Wadhwa, Shikha; Ghosh, B; Sarma, Sweety; Ray, Sekhar C; Kaviraj, Bhaskar; Roy, Susanta S; Roy, Saibal
Abstract: ' Co-filled ' and ' Fe-filled ' multiwall carbon nanotubes (MWCNTs) were grown using microwave-plasma chemical vapour deposition (MPCVD) and thermal chemical vapour deposition (TCVD) methods respectively, and their structural and magnetic properties were studied for magnetic device applications. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images show the average tube length ≈80–500 μ m with outer (inner) diameter ≈20–50 (≈10–20) nm for MWCNTs prepared by both methods. The diffraction peaks of both x-ray diffraction patterns show the interlayer distance, d 002 ≈ 3.36 Å, which is comparable to the graphite structure ( d 002 = 3.35 Å). The graphitic crystallite sizes ( L a ) of MPCVD (TCVD) synthesized MWCNTs are ≈24.78 nm (≈22.13 nm) as obtained from the intensity ratio of ( I D / I G ) D-peak, the disordered structure of graphite and G-peak, the C−C bond in graphitic structure of Raman spectra. The magnetization of ' Fe-filled ' TCVD grown MWCNTs is much higher than ' Co-filled ' MPCVD grown MWCNTs due to the formation of higher content of Fe–C and/or Fe-oxides in the MWCNT structures. The higher magnetic coercivity ≈2900 Oe and formation of isolated single-domain Fe-nanoparticles in ' Fe-filled ' TCVD grown MWCNTs, as found from SEM / TEM micrographs, makes the ferromagnetic MWCNTs a promising material for the high-density magnetic recording media.